Opinion leadership in an organization change context - Pajunen, Veli-Pekka (2021)
Opinion leadership phenomenon is widely used in marketing literature, especially from the view of diffusion of innovations. However, studies on social networks and leadership literature indicate that the opinion leadership phenomenon can be found from all parts of society. With an organizational view on the phenomenon, this case study research focuses on the opinion leadership phenomenon in an organizational change context.